Doodle diaries for enhancing students’ writing amidst technological era: A mixed methods study - Panggih Rahardi; Lilia Indriani (ELT Forum: Journal of English Language Teaching, 2025)
The use of technology can help students' current writing activities inside and outside the classroom. However, based on previous studies, there is still conflicting debate whether technology can help or hinder students in writing. As a result, some developed countries such as Australia and Sweden are de-emphasizing the excessive use of technology in academic settings and are turning back to printed books and texts to get students used to writing manually by hand. In this case, this study investigates deeply manual writing instruction using doodle diaries via paper and pencil in writing classes then how to correlates to their motivation. However, university students as participants in this study were not prohibited from using technology. Through mixed methods study, it was seen that some students were still looking for a technology assistant to help with their writing in their weekly doodle diary. Nevertheless, it was also shown that students have a positive view of this instruction and there is a significant improvement in their writing skills. On the other hand, this study also found that students' writing scores did not correlate significantly with their writing motivation. To obtain these findings, survey through questionnaires, interviews, and documentation along with inferential statistics and descriptive statistical techniques were employed. These findings also implicated that such manual writing instruction can still be employed in this technological era, but other aspect than writing motivation also need to be considered.